ANTESEDEN KEPATUHAN WAJIB PAJAK - , Nancy Mayriski Siregar (JURNAL PERPAJAKAN, 2020)
This research aimed to analyze the effect of e-filing, e-billing, e-factur, e-bupot on taxpayer compliance. This research applied a survey method using questionnaries distributed to the taxpayers. The total number of respondents was 93 taxpayers. The regression model used in this study is the linear regression models with SPSS. The result showed simultaneously e-filing, e-billing, e-factur, e-bupot have a significant effect on taxpayer compliance. Partially e-filing and e-bupot have not significant positive effect on taxpayer compliance, e-billing has no significant negative effect on taxpayer compliance, e-factur has a significant negative effect on taxpayer compliance.